The Impact of Aerobic Exercise and Cognitive Stimulation on Cognitive Function in the Elderly - Aula Reci; Rika Sabri; Siti Yuliharni (Indonesian Journal of Global Health Research, 2025)
The world's population, including Indonesia, is currently undergoing an aging process, characterized by an increase in the number and proportion of elderly individuals. The aging process leads to changes in physical health, sleep patterns, psychosocial well-being, and cognitive function in the elderly. Cognitive impairment poses a serious problem for older adults due to its physical, psychological, social, and economic impacts. Effective interventions can provide holistic support to elderly individuals with cognitive impairment, helping them to live better and more meaningful lives. This research aims to analyze the influence of aerobic exercise and cognitive stimulation on the improvement of cognitive function in the elderly. The research method used was an experimental study with a one-group pretest-posttest design. The sample was selected using a purposive sampling technique. The study sample consisted of 34 elderly individuals who met the inclusion criteria. The research instrument used the Mini Mental State Examination (MMSE) to measure the cognitive level of the elderly participant. Data were processed using SPSS and analyzed using the Wilcoxon Signed Rank Test.The results of the Wilcoxon signed-rank test showed that the average score of cognitive function experienced a significant increase between before and after the intervention, with a p-value of 0.000. Based on the findings of this study, aerobic exercise and cognitive stimulation have a positive influence on the improvement of cognitive function in the elderly.